Menumbuhkan Keberanian Berpendapat melalui Model Pembelajaran Kooperatif Think Pair Share - Endang Puji Lestari (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2014)
This research is to get courage on the arguments and to increase the result of the students learning in studying the opinion of freedom expression material to the seventh grade students H Junior High School Students 3 Taman Pemalang on the second semester in the academic year 2011/2012 through “think pair share” learning model. This research was conducted in to two cycles. The subjects of the research is the seventh grade students H SMP Negeri 3 Taman Pemalang, it is about 40 students. The data was collected by using a test. The test includes written test and non-test techniques such as observation, questionnaires and interview. The data were obtained and analyzed with descriptive comparative analysis. It is intended to compare between the first conditions and the result is achieved by the target. The result analysis shows that the courage opinion students in the learning process increasingly from pre-cycle (10 %), the first cycle (22.5 %) and the second cycle (55 %). The result student learning also increase from pre-cycle (40 %), the first cycle (57.5 %) and the second cycle (87.5 %). The above results show that the learning model think pair share is able to get courage on the argument and to increase the result student learning is higher 2.5 % than a pre-determined limit is completed 85 %.